Key terms of the Qur'an : a critical dictionary - Sinai, Nicolai, 1976- (Princeton University Press, 2023)
"A one-volume, single-authored reference book featuring scholarly essays on key terms that appear in the Qur'an"-- Provided by publisher.
Keywords: Qurʼan -- Dictionaries.; Qurʼan -- Terminology.; Qurʼan -- Language, style -- Terminology.; Qurʼan; Islam -- Terminology.; RELIGION / Islam / Koran & Sacred Writings; Islam; Electronic books.; Dictionaries; Terminology